Large size and low density SiOC aerogel monolith prepared from triethoxyvinylsilane/tetraethoxysilane. Issue 7 (May 2017) - Ma, Jie; Ye, Feng; Lin, Shaojie; Zhang, Biao; Yang, Haixia; Ding, Junjie; Yang, Chunping; Liu, Qiang
Abstract: Crack-free silicon oxycarbide (SiOC) aerogel monolith was fabricated by pyrolysis of precursor aerogel prepared from triethoxyvinylsilane/tetraethoxysilane (VTES/TEOS) using sol-gel process and ambient drying. Effects of different precursors, the amount of base catalyst (NH4 OH) and the heating rate during pyrolysis on the properties such as monolithicity, bulk density, surface area and pore size distribution of aerogels were investigated. The results show that the crack-free SiOC aerogel can be easily obtained from VTES/TEOS as compared to that of methyltriethoxysilanes/tetraethoxysilane (MTES/TEOS) and phenyltriethoxysilanes/tetraethoxysilane (PhTES/TEOS) precursors. The influence of heating rate during pyrolysis process on shrinkage rate, ceramic yield and surface area of the SiOC aerogels could be ignored, while the variation in the amount of NH4 OH exerted a strong impact on the properties of SiOC aerogels. Increasing the amount of NH4 OH resulted in the decrease of bulk density and surface area of SiOC aerogels from 0.335 g/cm 3 and 488 m 2 /g to 0.265 g/cm 3 and 365 m 2 /g. The resultant SiOC aerogels exhibit high compressive strength (1.45–3.17 MPa). 29 Si MAS NMR spectra revealed the retention of Si-C bond in the SiOC aerogels after pyrolysis at 1000 °C. The present work demonstrates VTES/TEOS is a promising co-precursors to easily and low cost synthesize large size SiOC aerogel monolith.